Network Governance dalam Layanan Tuberkulosis di Fasilitas Kesehatan Pemerintah dan Swasta berbasis Kabupaten/kota di Kota Pekanbaru - Yani Roslani br. Aritonang; Sujianto Sujianto (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Pekanbaru City as the capital of Riau Province shows an increasing number of tuberculosis cases, so it is necessary to strengthen the service network by involving government and private health service facilities based on districts/cities. The purpose of this study is to analyze and describe network governance in TB services in government and private health facilities based on districts/cities and their inhibiting factors. The method used in this study is a descriptive qualitative research method. With data collection techniques, namely interviews, observations, and documentation. The results of this study are that the governance of government networks in TB services in government and private health facilities based on districts/cities in Pekanbaru City has been running well but not optimally. This is due to several factors, namely the limited number of medical personnel and the lack of intensity of meetings between the actors involved.